2015
DOI: 10.1186/s12906-015-0795-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of substantial myocardial regeneration by an active fraction of the Chinese herb Rosa laevigata Michx

Abstract: BackgroundThe replacement of lost cardiac tissues by regenerated myocardium would be a therapeutic ideal for myocardial infarction. The objective of this study was therefore to evaluate the ability of an active fraction that was isolated from Rosa laevigata Michx in therapeutic cardiomyogenesis in a myocardial infarction rat model.MethodsThe myocardial infarction animal model was induced by the permanent ligation of the left anterior descending coronary artery in rats. The active fraction, which improves the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… Jia et al (2012) demonstrated the protective effects of TFs in R. laevigata against hydrogen peroxide-induced injury in human umbilical vein endothelial cells. Qu et al (2015) established a myocardial infarction (MI) rat model to study the ability of the active ingredients of R. laevigata in the treatment of this condition. The results showed oral administration of the active ingredients to MI-induced animals gradually restored the decline in cardiac function caused by MI and induced the myocardial regeneration and replacement of necrotic heart tissues.…”
Section: Pharmacologymentioning
confidence: 99%
“… Jia et al (2012) demonstrated the protective effects of TFs in R. laevigata against hydrogen peroxide-induced injury in human umbilical vein endothelial cells. Qu et al (2015) established a myocardial infarction (MI) rat model to study the ability of the active ingredients of R. laevigata in the treatment of this condition. The results showed oral administration of the active ingredients to MI-induced animals gradually restored the decline in cardiac function caused by MI and induced the myocardial regeneration and replacement of necrotic heart tissues.…”
Section: Pharmacologymentioning
confidence: 99%
“…Rosa laevigata (RL), which is mainly distributed in southern China and Asia, belongs to the Rosaceae family. RL fruit is edible and has been used in traditional medicine for the treatment of various diseases, including kidney disease and diarrhea ( Qu et al, 2015 ). According to recent research, numerous lignans with antioxidant activity and compounds such as flavonoids, saponins, and tannins have been isolated from the fruits of RL ( Li et al, 2012 ; Zhang et al, 2013d ; Dong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%